MODEL PENINGKATAN KINERJA REKSADANA SYARIAH BERBASIS STOCK SELECTION SKILL, EXPENSE RATIO DAN TINGKAT RISIKO - Harminingtyas, Rudika; Susetyarsi, Th (JURNAL STIE SEMARANG, 2021)
Abstract. This study to determine how the Syariah Mutual Fund Performance Improvement Model Based on Stock Selection Skill, Expense Ratio, and Risk Level. The population in this study were syariah mutual fund investment managers in a certain period of time, from 2010 to 2018 and a sample of 30 Islamic mutual funds was taken with a purposive sampling method.Data Collection techniques are carried out by documentation and literature study methods. Data analysis techniques use regression analysis and also use Moderated Regression Analysis (MRA) to test the relationship between the independent variable and the dependent variable. Based on the results of the calculation, it is obtained that the Stock Selection results have a t value of 1.161 and the significance value of the syariah mutual funds performance variable is 0.235, greater than 0.05(H1 Accepted).The Stock Selection results have a t value of 1.161 and the significance value of the Expense Ratio is 0.335, greater than 0.05(H2 Accepted).The Expense Ratio has a t value of 0.835 and the significance value of the expense ratio variable is 0.400, greater than 0.05(H3 Accepted). The MRA test results show that the significance level of the moderating variable Stock Selection * ExpenseRatio shows a value of 0.221, which means the significance is> 0.05. The Expense Ratio has a t value of 0.835 and the significance value of the expense ratio variable is 0.400, greater than 0.05. The MRA test results show that the significance level of the moderating variable Stock Selection * ExpenseRatio shows a value of 0.221, which means the significance is> 0.05. The results of the Sobel test, the value of t count = 0.68603298 is smaller than the t table with a significance of 0.05, which is 1.980, so it can be concluded that the mediation coefficient is 0.68603298 and the probability value is 0.49269231 greater than 0.05( H5 is rejected). The level of risk has a t value of 0.571 and the significance value of the risk level variable is 0.545 which is smaller than 0.05(H4 accepted),The test results of the significance level of the moderating variable Stock Selection * The level of risk shows the value of 0.345 which means the significance is> 0.05. . The results of the Sobel test, based on the results of the calculation above, the t value = 0.52454261 is smaller than the t table with a significance of 0.05, which is 1.980, it can be concluded that the mediation coefficient is 0.52454261 and the probability value is 0.59990119 greater than 0.05(H6 is rejected). Abstrak. Penelitian ini bertujuan untuk mengetahui bagaimana Model Peningkatan Kinerja Reksadana Syariah Berbasis Stock Selection Skill,,Expense Ratio,dan Tingkat Resiko.Populasi adalah manajer investasi reksadana syariah kurun waktu tahun 2010 hingga 2018 dan diambil sampel sebanyak 30 reksadana Syariah dengan metode purposive sampling.Teknik pengumpulan dengan metode dokumentasi dan studi kepustakaan.Teknik analisis data menggunakan analisis regresi dan Moderated Regression Analysis (MRA) untuk menguji hubungan antara variabel independen dengan variabel dependen. Hasil perhitungan sebagai berikut, Stock Selection mempunyai nilai t sebesar 1,161 dan nilai signifikansi variabel kinerja reksadana syariah adalah sebesar 0,235 lebih besar dari 0,05 ( H1 diterima). Hasil Stock Selection mempunyai nilai t sebesar 1,161 dan nilai signifikansi variabel Expense Ratio sebesar 0,335 lebih besar dari 0,05, (H2) diterima. Expense Ratio mempunyai nilai t sebesar 0,835 dan nilai signifikansi variabel expense ratio sebesar 0,400 lebih besar dari 0,05( H3 diterima).Hasil uji MRA, tingkat signifikansi variabel moderasi StockSelection*ExpenseRatio menunjukkan hasil nilai 0,221 yang berarti signifikansinya > 0,05. Hasil uji Sobel nilai t hitung = 0,68603298 lebih kecil dari t table dengan signifikansi 0,05 yaitu sebesar 1,980 maka dapat disimpulkan koefesien mediasi 0,68603298 dan nilai probability 0,49269231 lebih besar dari 0,05(H4 ditolak). Tingkat Resiko mempunyai nilai t sebesar 0,571 dan nilai signifikansi variabel Tingkat Resiko sebesar 0,545 lebih kecil dari 0,05, ( H5 diterima) Hasil uji tingkat signifikansi variabel moderasi StockSelection*TingkatResiko menunjukkan hasil nilai 0,345 yang berarti signifikansinya > 0,05. . Hasil uji Sobel, berdasarkan hasil perhitungan di atas nilai t hitung = 0,52454261 lebih kecil dari t table dengan signifikansi 0,05 yaitu sebesar 1,980 maka dapat disimpulkan koefesien mediasi 0,52454261 dan nilai probability 0,59990119 lebih besar dari 0,05 ( H6 ditolak).